Deployment of Webgis Spread Location Natural Resources of Labuhanbatu Regency - Sigit Prasetyo Nugroho; Ibnu Rasyid Munthe; Syaiful Zuhri Harahap (Institute of Computer Science (IOCS), 2021)
Natural resources abound in the Labuhanbatu region of North Sumatra. Natural resources are plentiful in the district. The labuhanbatu were unaware of their abundance of natural resources. We will establish dominion over Labuhanbatu's location and abundance of natural resources. Utilizing Geographic Information Systems (or GIS, as it is more commonly known) in an ever-changing internet environment. People are constantly seeking access to data, and the Labuhanbatu community will benefit from GIS (Geographic Information System). Create an interactive map of the subdistrict's natural resources for the benefit of nearby residents. Collecting data in a GIS may or may not be easy. Additionally, horticulture, poultry, plantations, and fisheries are included, as are natural resources that benefit the soil.